How functional movement variability facilitates successful skill adaptation during the volleyball attack - Caldeira, P.; Paulo, A.; Veloso, A.; Infante, J.; Davids, K.; Araújo, D. (International Journal of Sports Science & Coaching, 2023)
From an ecological dynamics perspective, careful manipulation of task constraints can provide opportunities for action, exploited by functional movement variability of participants. The constraints-led approach (CLA) induces functional movement variability in practice designs, supporting athlete performance in satisfying task constraints and finding performance solutions to achieve intended task goals. Young male volleyball players were randomly assigned to either a traditional approach (TA) or CLA practice group. Selected spatial-temporal movement coordination variables were recorded, to explore their relations to successful performance outcomes in the attacking phase. Binomial logistic regression was used to verify the association of spatial-temporal movement variables with the percentage of successful attacks. Six spatial-temporal variables were included, and a manual backward stepwise regression was used to remove those which did not contribute to the best predictive model of successful performance. After a 6-week intervention programme, the CLA practice group displayed a significantly higher percentage of successful attack actions, when facing the opposition block. The TA group showed a small increase in successful attack actions after the intervention. The final binomial logistic regression model revealed that the variables `lateral deviation of the participants` centre of mass` at the planting step and `longitudinal deviation of the participants` centre of mass` at point of ball contact were the main predictors of successful attacking outcomes. To overcome the opposition's block in volleyball, infusing functional variability in a CLA task design, promoted superior performance in practice. Presumably, greater movement pattern variability emerged in participants to satisfy performance constraints in successful volleyball attacks.